Palmar process fractures of the distal phalanx in foals: A review. (12th November 2015) - Faramarzi, B.; Dobson, H.
Summary: Distal phalanx fractures are well documented in adult horses, but our knowledge of such fractures in foals is limited. Recent studies showed a high incidence of distal phalanx palmar process (PP) fractures in foals, the aetiology is not yet known. Several hypotheses have been suggested as possible causes, including uneven compressive forces, unequal forces from the deep digital flexor tendon, composition and shape of the PP, and conformation. A better understanding of the aetiology and predisposing factors requires further research. Radiography is the commonly used imaging modality for diagnosis of such fractures; however, those fractures might be missed on routine radiographic projections. In order to have a high probability of identifying fractures, a series of 5 radiographs including the oblique views is required. This article reviews the incidence of distal phalanx PP fractures and discusses the diagnosis of such fractures.